Proportional Epidemic Models on Time Scales - Yılmaz, Emrah; Tokay, Gülcan (My University, 2025)
In this study, some epidemic models such as SI (Susceptible-Infectious), SIR (Susceptible-Infectious-Recovered), and SIS (Susceptible-Infectious-Susceptible) have been formulated using proportional derivative on time scales, and solutions have been obtained through the application of time scale analysis techniques and proportional derivative rules.
Keywords: Epidemic models; Proportional derivative; Time scales